Cut-Off Effect of Radical Tempo Derivatives in Olive Oil-In-Water Emulsions - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C (Elsevier Ltd, 2017)
Three oil-in-water emulsions were prepared from mixtures of olive oil and Tween 20 in water. The effectiveness of a series of radical 2,2,6,6-tetramethylpiperidinoxyl (TEMPO) derivatives of variable lipophilicity in reactions with antioxidant Trolox, and as pyrene-fluorescence quenchers, was compared in the three emulsions. A “cut-off” effect was observed for the pyrene quenching by the probes, but not for their reaction with Trolox. The results were rationalized in terms of the amphiphobic nature of the probes, and the different locations of probe, pyrene and Trolox in the three-phase microheterogeneous systems. © 2016 Elsevier Ltd